Improving Detection of Underlying Neurologic Etiology for Pediatric Cavovarus Foot Deformity: We Can Do Better - Michael O'Sullivan MD; Michelle Christie MD; Rusty Hartman BS; Anthony I. Riccio MD (Foot & Ankle Orthopaedics)
Category: Other; Midfoot/Forefoot Introduction/Purpose: While evaluation of an underlying neurologic disorder in children with cavovarus foot deformity (CVD) is of great importance, no standardized method of neurologic assessment exists. Moreover, the yield of commonly employed diagnostic measures remains unstudied. This study aims to compare the diagnostic yield of traditional methods of neurologic assessment for patients CVD of unknown etiology to a more advanced diagnostic algorithm. Methods: An IRB-approved retrospective review of patients presenting to a single pediatric tertiary care center for bilateral or unilateral CVD was performed over a 19-year period. Patients with a known etiology for their deformity or preexisting neurologic or syndromic diagnoses were excluded. Neurologic evaluation of all remaining patients was conducted by a pediatric neurologist using one of two diagnostic algorithms. The traditional diagnostic algorithm (TDA) consisted of clinical examination, MRI of the brain and spinal cord and/or EMG/NCV. The advanced diagnostic algorithm (ADA) Included all components of the TDA in addition to genetic testing, and/or muscle/nerve biopsy and/or repeat EMG/NCV testing when initial workup remained negative. These diagnostic algorithms were compared regarding determination of an underlying etiology for CVD. Results: 108 patients (average age 9.7 years) were included. 96 were assessed via the TDA which detected an underlying neurologic diagnosis in 56 (58%). 15 had central neurologic disease, 35 had peripheral neuropathies and 6 had combined central/peripheral neuropathology. Of the 40 patients in whom no diagnosis was made using the TDA, 21 were further assessed using the ADA revealing a diagnosis in 15 (71%), thereby increasing the diagnostic yield to 71/77 patients (92%) when the ADA was incorporated and 71/96 (74%) overall. Moreover, 23 of 41 patients (56%) diagnosed with an unspecified polyneuropathy by TDA received a more specific diagnosis via the ADA. Definitive diagnosis was achieved solely by genetic testing without the TDA in 12 patients, 75% of whom had variants of Charcot-Marie-Tooth disease. Conclusion: Neurologic etiology remains undetected in 42% of children with CVD using solely neuroaxis imaging and electrodiagnostic testing. Determination of an underlying neurologic cause for deformity can be increased by over 30% through the incorporation of genetic testing and other components of the ADA.